Tacrolimus for Ophthalmic Use: An Update - Sana Ilias Tinwala; Himanshu Shekhar; Sandeep Gupta; Rajesh Sinha; Jeewan S Titiyal (Delhi Journal of Ophthalmology)
Tacrolimus, a macrolide isolated from a strain of Streptomyces, is an immunosuppressant and is used in cases of organ transplantation. It has a mechanism of action similar to that of cyclosporine. It is a lipophilic molecule which blocks the early phase of T-cell activation, thus inhibiting both T-lymphocyte signal transduction and IL-2 transcription. It is also inhibits the release of histamine from mast cells and impairs prostaglandin synthesis. Tacrolimus has shown to be effective in the treatment of immune-mediated diseases such as corneal graft rejection, ocular inflammation, ocular pemphigoid, and uveitis. In this article, we have tried to update the uses of tacrolimus in ophthalmology.